Analisis Ukuran Perusahaan, Audit Tenure, Dan Leverage Terhadap Opini Audit Going Concern Pada Perusahaan Sektor Manufaktur Yang Terdaftar Pada BEI Periode 2019-2021 - Mardiyanto, Doni; Hastuti, Fitri Ari (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to determine the effect of company size, audit tenure and leverage on going concern audit opinions in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period, either partially or simultaneously. This research is a quantitative research. The sampling technique used was purposive sampling by taking secondary data from the www.idx.co.id page. The population of this research is 183 companies where 68 companies are the sample. The analysis technique used is descriptive statistics, panel data regression analysis, panel data regression model, panel data regression model selection and hypothesis testing. The results of this study state that: company size has no effect on going-concern audit opinion, tenure audit has no effect on going-concern audit opinion, leverage has a negative effect on going-concern audit opinion. firm size, audit tenure and leverage have a simultaneous effect on going concern audits.